Amiridine-piperazine hybrids as cholinesterase inhibitors and potential multitarget agents for Alzheimer's disease treatment - Makhaeva, Galina F; Lushchekina, Sofya V; Kovaleva, Nadezhda V; Yu Astakhova, Tatiana; Boltneva, Natalia P; Rudakova, Elena V; Serebryakova, Olga G; Proshin, Alexey N; Serkov, Igor V; Trofimova, Tatiana P; Tafeenko, Victor A; Radchenko, Eugene V; et al. (Bioorganic chemistry, 2021)
We synthesized eleven new amiridine-piperazine hybrids 5a-j and 7 as potential multifunctional agents for Alzheimer's disease (AD) treatment by reacting N-chloroacetylamiridine with piperazines. The compounds displayed mixed-type reversible inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Conjugates were moderate inhibitors of equine and human BChE with negligible fluctuation in anti-BChE activity, whereas anti-AChE activity was substantially dependent on N4-substitution of the piperazine ring. Compounds with para-substituted aromatic moieties (5g, 5h, and bis-amiridine 7) had the highest anti-AChE activity in the low micromolar range. Top-ranked compound 5h, N-(2,3,5,6,7,8-hexahydro-1H-cyclopenta[b]quinolin-9-yl)-2-[4-(4-nitro-phenyl)-piperazin-1-yl]-acetamide, had an IC50 for AChE = 1.83 ± 0.03 μM (Ki = 1.50 ± 0.12 and αKi = 2.58 ± 0.23 μM). The conjugates possessed low activity against carboxylesterase, indicating a likely absence of unwanted drug-drug interactions in clinical use. In agreement with analysis of inhibition kinetics and molecular modeling studies, the lead compounds were found to bind effectively to the peripheral anionic site of AChE and displace propidium, indicating their potential to block AChE-induced β-amyloid aggregation. Similar propidium displacement activity was first shown for amiridine. Two compounds, 5c (R = cyclohexyl) and 5e (R = 2-MeO-Ph), exhibited appreciable antioxidant capability with Trolox equivalent antioxidant capacity values of 0.47 ± 0.03 and 0.39 ± 0.02, respectively. Molecular docking and molecular dynamics simulations provided insights into the structure-activity relationships for AChE and BChE inhibition, including the observation that inhibitory potencies and computed pKa values of hybrids were generally lower than those of the parent molecules. Predicted ADMET and physicochemical properties of conjugates indicated good CNS bioavailability and safety parameters comparable to those of amiridine and therefore acceptable for potential lead compounds at the early stages of anti-AD drug development.
Keywords: oxidační stres; Cholinesterase Inhibitors; antioxidancia; Piperazine; aminochinoliny; neuroprotektivní látky; Structure-Activity Relationship; Molecular docking; molekulární struktura; Amiridine; Molecular Structure; vztah mezi dávkou a účinkem léčiva; Alzheimerova nemoc; Alzheimer Disease; Neuroprotective Agents; Butyrylcholinesterase (BChE); acetylcholinesterasa; ADMET; molekulární modely; benzothiazoly; vztahy mezi strukturou a aktivitou; Models, Molecular; Multifunctional agents; Benzothiazoles; Animals; lidé; Antioxidants; Humans; Butyrylcholinesterase; zvířata; Acetylcholinesterase (AChE); koně; Aminoquinolines; Molecular dynamics (MD) simulations; kyseliny sulfonové; Alzheimer’s disease (AD); butyrylcholinesterasa; Sulfonic Acids; Oxidative Stress; piperazin; Acetylcholinesterase; cholinesterasové inhibitory; Dose-Response Relationship, Drug; Horses